Biến thể cú pháp tỉnh lược thành tố từ góc nhìn chức năng = Ellipsis: syntactic variations / Dương Xuân Quang. - Dương, Xuân Quang.
Ellipsis is a phenomenon that has many linguists interested in Vietnamese language. However, Vietnamese linguists research ellipsis from structural and formal perspective. In our opinion, an ellipsis is a syntactic variant. This variant is affected by functions, as: emphasizing important information (focus), expressing the attitude of the speaker, and maintaining coherence of utterances in discourse. This article will discuss this phenomenon by explanation them from functional perspective.